Siebeck curves and two refinements of the - Casas-Alvero, Eduardo (MATHEMATICA SCANDINAVICA, 2012)
We prove two results which improve the well known Gauss-Lucas theorem by locating the roots of the derivative of a complex polynomial f in sets smaller than the convex hull of the roots of f.